Epidemiological perspective of National Leprosy Eradication Programme in Maharashtra: Focusing on “Tribal Hot-spot” of Tribal District - Dhananjay Katkar; Balu Natha Mote; Ambadas Adhav; Thirumugam Muthuvel; Suhas Kadam (Indian Journal of Community Medicine, 2017)
Background: Leprosy or Hansen's disease, a chronic infectious disease caused by Mycobacterium leprae is a serious public health concern because of associated case load, morbidity and stigma attached to it. India achieved elimination of leprosy as a public health problem (prevalence rate [PR]<1 case/10,000 population) at the national level on January 1, 2006, still 19% districts in the country report PR more than one. In Maharashtra, it is found that very few districts within the state or very few pockets within the district are actually having leprosy burden. Objectives: (1) Identification of region-wise actual “hot-spot” districts/pockets within state of Maharashtra.(2) Further drop-down below the district and block to tribal belt for understanding the actual high risk area/belt within the tribal districts. Methods: Secondary data analysis of leprosy patients registered in the State during the period 2008–2015. Results: PR per 10,000 was found more in Vidharbha region followed by rest of Maharashtra and then Marathwada. Analysis showed that, there are tribal districts and tribal area within tribal districts which are having higher leprosy burden as compared to the all other districts indicating need of allocation of programme funds and facilities to these tribal belts for the effective control and elimination of leprosy. Conclusion: National Leprosy Eradication Programme should focus on tribal belt for effective control. Without giving extra attention to these tribal areas within high risk district/pockets efforts of eradication of leprosy by 2018 would be unrealistic and impractical.